(untitled) (KULT_online, 2021)
As one of the most prominent intellectuals of the pre-revolutionary era, Jalal Al-e Ahmad (1923–1969) had left a lasting legacy in his homeland Iran and beyond. After his passing, Al-e Ahmad has steadily been subjected to various post-mortem inquiries, debates and oftentimes controversies. Throughout The Last Muslim Intellectual: The Life and Legacy of Jalal Al-e Ahmad, Hamid Dabashi offers a critical appraisal of Al-e Ahmad’s life and writings. He predicates this appraisal on both his perceptive insights and comprehensive research.